Influência da adição de Nb e da atmosfera de solidificação nas propriedades estruturais, térmicas, mecânicas e magnéticas de uma liga Heusler NiMnSn - Silva, Fernanda de Souza (2022)
The Heusler Ni50Mn50-xYx alloys (Y = Sb, Sn and In) have drawn the attention of many researchers in recent years due to their great application potential. For some critical range of Y concentration these alloy systems are found to undergo martensitic phase transformation from a high temperature cubic phase (austenite) to a low temperature orthorhombic phase (martensite). Notoriously, by evaluating the concentrations, the alloy production processes, as well as the applied heat treatments, it is possible to obtain promising properties in these materials, including large magnetic entropy changes, and giant magnetoresistance, for example. In this work it was reported a systematic investigation of the structural, thermal, and magnetic properties of Ni50Mn37Sn13 Heusler alloy obtained by fusion without controlled atmosphere and annealing. Specifically, was produced Ni50Mn37Sn13 (atomic percentages - a.%) alloy sample by induction casting and characterize them by X‑ray diffraction, differential thermal analysis, and magnetometry. The results bring to light an interesting way to minimize the processing costs of NiMnSn alloy, inherent to vacuum systems and protection with inert gas. Besides, it was possible to show that the studied alloy retains the thermal and magnetic properties observed in other processing routes, thus making it a promising candidate for technological applications. Within this same scope, with the objective of deepening our study regarding Heusler NiMnSn alloys, three NiMnSnNb alloys were produced, so that 1%at of niobium replaces 1%at of Sn in the first alloy, replaces 1%at of Ni in the second alloy and 1%at of Mn in the third alloy. These alloys were produced under argon controlled atmosphere and characterized by X-ray diffraction, Vickers microhardness assay, EDS (energy dispersive spectroscopy) and magnetometry. Regarding the processing of NiMnSn alloy without atmosphere control, our results reveal that despite the differences in structural and thermomagnetic properties between the upper and lower regions of the ingot, the values presented for these properties are compatible with those verified in the literature and with the alloy of the same composition produced in a controlled atmosphere. The modification of the Heusler NiMnSn system with the addition of Nb revealed that the partial replacement of the elements Ni, Mn and Sn by Nb did not change the dendritic microstructure and the ferromagnetic ordering obtained for the alloys of the NiMnSnNb system. An increase in Vickers microhardness was also observed with the addition of Nb in the alloys. Thus, our results bring to light an interesting way to minimize the processing costs of the alloy of the NiMnSn system, inherent to vacuum and inert gas protection systems, as well as, present a new alternative to the doping of the NiMnSn alloy, as a way to modify the structural and magnetic properties, interesting parameters for technological applications.